1997
DOI: 10.1002/(sici)1097-0029(19970815)38:4<428::aid-jemt10>3.0.co;2-l
|View full text |Cite
|
Sign up to set email alerts
|

Elastic fiber during development and aging

Abstract: Elastin molecules aggregate in the extracellular space where they are crosslinked by stable desmosine bridges. The resulting polymer is structurally organized as branched fibers and lamellae, which, in skin, are wider (a few microns) in the deep dermis and become progressively thinner (fraction of a micron) towards the papillary dermis. Several general and local factors seem to regulate elastin gene expression, deposition and degradation. In skin, the volume density of the elastin network increases from birth … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
102
1
1

Year Published

2000
2000
2019
2019

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 176 publications
(108 citation statements)
references
References 70 publications
4
102
1
1
Order By: Relevance
“…The RAGE-dependent lung function suggested an effect of RAGE on the lung elasticity, which is determined by surfactants and extracellular matrix proteins (33), including elastin and collagen (8,35). Although RAGE had no effect on the mRNA expressions of surfactant proteins (gene microarray analysis; data not shown), we found a lower mRNA and protein level of elastin in young RAGE-KO mice than in WT mice (Tables 3 and 4, Fig.…”
Section: Rage Trans Interaction In Alveolar Epithelial Cellsmentioning
confidence: 68%
“…The RAGE-dependent lung function suggested an effect of RAGE on the lung elasticity, which is determined by surfactants and extracellular matrix proteins (33), including elastin and collagen (8,35). Although RAGE had no effect on the mRNA expressions of surfactant proteins (gene microarray analysis; data not shown), we found a lower mRNA and protein level of elastin in young RAGE-KO mice than in WT mice (Tables 3 and 4, Fig.…”
Section: Rage Trans Interaction In Alveolar Epithelial Cellsmentioning
confidence: 68%
“…Once laid down, they are thought to remain stable 2 , except in the uterine tract where cycles of active remodeling occur 3 . Loss of elastic fibers underlies connective tissue aging and important diseases including emphysema [4][5][6][7] . Failure to maintain elastic fibers is explained by a theory of antielastase-elastase imbalance 8 , but little is known about the role of renewal.…”
mentioning
confidence: 99%
“…Immunohistochemical studies on human skin have suggested that decorin may be associated with fibrillin-containing, elastin-associated microfibrils, whereas biglycan may be associated with the elastin core of the elastic fibers (10,11). Kielty et al (12) have shown that chondroitinase AC treatment disrupts the bead component of fibrillin-containing microfibrils and that a chondroitinase AC-sensitive proteoglycan can be co-precipitated with fibrillin from smooth muscle cell conditioned medium.…”
mentioning
confidence: 99%